Queen Helen and King Michael: The Beginning of a New Dynasty? - Budak, Neven (ASPICE HUNC OPUS MIRUM: zbornik povodom sedamdesetog rođendana Nikole Jakšića, 2020)
Queen Helen is the single example of a Croatian queen about whom we have two independent sources: her epitaph and a mention by Thomas the Archdeacon of Split. Similarly, her husband, king Michael Krešimir II is also documented by his wife’s epitaph, by Constantine Porphyrogenitus, and a charter issued by his great-grandson Peter Krešimir IV. This cannot be accidental and the aim of this article is to argue that the ascendance of the royal couple to the Croatian throne meant the beginning of a new dynasty. This change was supported by the establishment of the memory of the couple through Helen’s foundation of a royal mausoleum and the composition of a book of deeds of the king and his descendants.